Fraud detection in E-commerce using natural language processing - Kabir, Iftekhar; Momo, Marium Khan; Tazrian, Tahsin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.